Acute haemodynamic impact of transcatheter aortic valve implantation in patients with severe aortic stenosis - Francesca Graziani; Pio Cialdella; Rosa Lillo; Gabriella Locorotondo; Lorenzo Genuardi; Gessica Ingrasciotta; Stefano Cangemi; Marialisa Nesta; Piergiorgio Bruno; Cristina Aurigemma; Enrico Romagnoli; Michele Calabrese; et al. (ESC Heart Failure)
Abstract Aims There are limited data about the intraprocedural haemodynamic study performed immediately before and after transcatheter aortic valve implantation (TAVI) in patients with severe aortic stenosis (AS). We aimed to evaluate the acute haemodynamic impact of TAVI in patients with severe AS and to investigate invasive and non‐invasive parameters predicting all‐cause mortality. Methods and results A total of 245 consecutive AS patients (43% male, mean age 80.3 ± 7.3 years) undergoing TAVI were enrolled. Intraprocedural left heart catheterization (LHC) and echocardiogram before and after TAVI were performed. The clinical endpoint was the death for any cause. LHC after TAVI revealed significant changes in aortic and left ventricular (LV) pressures, including indexes of intrinsic myocardial contractility and diastolic function such as positive dP/dT (1128.9 ± 398.7 vs. 806.3 ± 247.2 mmHg/s, P ˂ 0.001) and negative dP/dT (1310.7 ± 431.1 vs. 1075.1 ± 440.8 mmHg/s, P ˂ 0.001). Post‐TAVI echo showed a significant reduction in LV end‐diastolic (P = 0.036) and end‐systolic (P ˂ 0.001) diameters, improvement in LV ejection fraction (from 55 ± 12% to 57.2 ± 10.5%, P ˂ 0.001), and pulmonary artery systolic pressure (42.1 ± 14.2 vs. 33.1 ± 10.7 mmHg, P < 0.001). After a mean follow‐up time interval of 24 months, 47 patients died. Post‐TAVI significant aortic regurgitation at echocardiography was the only independent predictor of mortality (hazard ratio 5.592, confidence interval 1.932–16.184, P = 0.002). Conclusions Left heart catheterization performed immediately before and after prosthesis release offers a unique insight in the assessment of LV adaptation to severe AS and the impact of TAVI on LV, catching changes in indexes of intrinsic contractility and myocardial relaxation. Aortic regurgitation assessed by echocardiography was the only independent predictor of mortality in patients undergoing TAVI.